Coupled Tropical Cyclone-ocean Modeling for Transition to Operational Predictive Capabilities - Ginis, Isaac; Rothstein, Lewis M (1997)
Our long term fundamental goals are I) to better understand the interaction between the ocean and tropical cyclones using numerical simulation models, and II) to investigate the operational capability of coupled tropical cyclone-ocean models in predicting the ocean response and tropical cyclone movement and intensity.